Agricultural Resource Depletion and Arising Concerns of Environmental Ethics in Punjab: A Dire Need of Rescue, Revival and Sustainable Development: Exploring the Impact of Agricultural Practices on Punjab's Environment and Ethics (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Today, it is a well-established fact that growing environmental complexities and concerns are an integral part of the overall process of sustainable development. Degradation of the environment, as a matter of fact, has been associated with almost every human action. At the threshold of 21st century, when we are at the verge of facing a global environmental crisis, with situations like global warming, climate change, draughts and frequent environmental calamities on the rise, man has finally begun to realise the ill consequences of his conscious and unconscious activities, most of which had been to satisfy and satiate his never ending greed and desires. The once harmonious relationship between man and environment today stands at crossroads, marred due to increased human greed, prominence of materialism, consumerism, individualism and egoism, ruthless misuse and waste of nature and natural resources, irresponsible and uncontrolled use of technology and indifference towards environment. Therefore, study and practice of environmental ethics have become very relevant today. Agriculture has been the most important human enterprise since the arrival of mankind on earth. It has been that productive unit of human survival where man has been getting the bountiful free gifts of nature, in abundance, such as land, light, water, air, weather, temperature, humidity and rainfall. It is the primary unit indispensable for human existence that produces food, feed, fuel, fibre and other valuable products through the cultivation of plants and domestication of animals. But alas! What has happened to this little, yet, the most developed creature called humans? Why have there been so much of ignorance, insensitivity, insanity and indifference? How could men think of their existence in seclusion…apart, aloof and away from nature? This paper seeks to look into some of these pressing questions giving special reference to the agricultural practices of Punjab and multiple problems arising henceforth, like- soil erosion, siltation and saltification; water contamination and depletion; and prominence of cancer and other life-taking diseases in the great land of green revolution. It also seeks to study the newer environmental and ethical concerns that have arrived before both, the peasant as well as the normal people of Punjab due to intensive agriculture, excessive use of chemical fertilizers, unscientific and over use of deadly chemical pesticides and many more bad practices prevalent in Punjab.